1997
DOI: 10.1007/bf01438307
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effects of interleukin-12 upon tumor-infiltrating lymphocytes derived from renal cell carcinoma

Abstract: Clinical trials utilising interleukin (IL)-2 with tumor-infiltrating lymphocytes (TIL) have demonstrated efficacy in the treatment of metastatic renal cell carcinoma (RCC). Several cytokines, as well as growth factors have demonstrated modulatory effects upon the biological properties of TIL from RCC, suggesting a potentially important role for cytokines other than IL-2 in the development of active and tumor-specific TIL. IL-12 was recently characterized as a natural-killer-cell-stimulatory factor or cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This trial has been cancelled prior to yielding any positive results. In preclinical studies, TIL that had been freshly isolated from tumors, expanded and activated by IL-2 treatment in culture showed considerable antitumor activity against renal carcinoma cells in vitro [25] as well as in different murine tumor models [26]. However, the normal tumor microenvironment is likely to have important influences upon TIL, as it has been shown that larger tumors have an immunosuppressive effect on lymphocytes [27].…”
Section: Discussionmentioning
confidence: 99%
“…This trial has been cancelled prior to yielding any positive results. In preclinical studies, TIL that had been freshly isolated from tumors, expanded and activated by IL-2 treatment in culture showed considerable antitumor activity against renal carcinoma cells in vitro [25] as well as in different murine tumor models [26]. However, the normal tumor microenvironment is likely to have important influences upon TIL, as it has been shown that larger tumors have an immunosuppressive effect on lymphocytes [27].…”
Section: Discussionmentioning
confidence: 99%